64Cu-DOTHA2-PSMA, a Novel PSMA PET Radiotracer for Prostate Cancer with a Long Imaging Time Window - Marie-Christine Milot; Ophélie Bélissant Benesty; Véronique Dumulon-Perreault; Samia Ait-Mohand; Patrick O. Richard; Étienne Rousseau; Brigitte Guérin (MDPI AG, 2022)
Prostate cancer imaging and late-stage management can be improved with prostate-specific membrane antigen (PSMA)-targeting radiotracers. We developed a PSMA positron emission tomography (PET) radiotracer, DOTHA2-PSMA radiolabeled with 64Cu (T1/2: 12.7 h), to leverage its large imaging time window. This preclinical study aimed to evaluate the biological and imaging properties of 64Cu-DOTHA2-PSMA. Its stability was assessed in plasma ex vivo and in mice. Cellular behavior was studied for up to 48 h in LNCaP cells. Biodistribution studies were performed in balb/c mice for up to 48 h. Dynamic (1 h) and static (4 h and 24 h) PET imaging was completed in LNCaP tumor-bearing mice. 64Cu-DOTHA2-PSMA was stable ex vivo in plasma and reached cellular internalization up to 34.1 ± 4.9% injected activity (IA)/106 cells at 48 h post-injection (p.i.). Biodistribution results showed significantly lower uptake in kidneys than 68Ga-PSMA-617, our reference PET tracer (p < 0.001), but higher liver uptake at 2 h p.i. (p < 0.001). PET images showed 64Cu-DOTHA2-PSMA's highest tumoral uptake at 4 h p.i., with a significant difference between blocked and non-blocked groups from the time of injection to 24 h p.i. The high stability and tumor uptake with a long tumor imaging time window of 64Cu-DOTHA2-PSMA potentially contribute to the prostate cancer theranostic approach and its local recurrence detection.